LIVING WITH MENIERE’S DISEASE: HOW TO MANAGE THIS CHALLENGING BALANCE AND HEARING DISORDER - Agnieszka Floriańczyk; Ewa Romanowicz; Aleksandra Kołdyj; Agnieszka Ozdarska; Adrian Krzysztof Biernat; Marcin Lampart; Anna Rupińska; Katarzyna Kozon; Kamila Krzewska (International Journal of Innovative Technologies in Social Science, 2025)
Meniere’s disease is a chronic inner ear disorder characterized by recurrent vertigo, fluctuating hearing loss, tinnitus, and aural fullness. Despite extensive research, its aetiology remains unclear, complicating treatment. This review summarizes current therapeutic strategies for Meniere’s disease, spanning non-pharmacological, pharmacological, intratympanic, and surgical interventions. Lifestyle modifications, such as salt restriction and increased water intake, offer initial symptom control, though evidence remains limited. Pharmacological therapies, including diuretics, betahistine, and piracetam, provide varying degrees of vertigo relief, with inconsistent outcomes for hearing and tinnitus. Intratympanic treatments—steroids and gentamicin—are effective for refractory cases; steroids offer hearing preservation, while gentamicin achieves superior vertigo control at the risk of ototoxicity. Surgical options, including endolymphatic sac shunt surgery, semicircular canal plugging, vestibular neurectomy, and labyrinthectomy, are reserved for intractable cases, with selection guided by disease severity and hearing status. Emerging therapies, such as vestibular rehabilitation and Coriolus versicolor supplementation, show potential in improving vestibular compensation and reducing oxidative stress and inflammation. While current treatments primarily aim to manage symptoms rather than resolving the underlying disorder, ongoing research may lead to more targeted and disease-modifying therapies.